Test tube families : why the fertility market needs legal regulation - Cahn, Naomi R. (New York : New York University Press, 2016)
How should the use of gametic material be regulated? Should recipients be able to choose the best sperm and eggs? Should a child ever be able to discover the identity of her gamete donor? Who can claim parental rights? This book explores these and other questions regarding assisted reproductive technology.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Fertilization in vitro, Human -- Law and legislation -- United States; Law; Laws of specific jurisdictions & specific areas of law; Medical ethics & professional conduct; Medicolegal issues; Infertility & fertilization